ENHANCING TOURISM ACCESSIBILITY IN BATAM CITY THROUGH SMART SUSPENDED MONORAIL ROUTE MODELLING - Livvy Rinoa; Hendro Murtiono; Stivani Ayuning Suwarlan; Andri Irfan Rifai (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
The transportation fulfils as the support of human activity and is the leading factor for economy as well as tourism development. Batam City, positioned strategically close to Singapore and Malaysia, is confronted with severe problems in urban mobility after experiencing a rapid rise in population and the inflow of international tourists. The low capacity of Trans Batam and infrastructure development stagnation have restricted tourism access, calling for urgent new and sustainable solutions for transportation. In this research, an integrated suspended monorail route in the framework of the Smart City will be designed to enhance tourism connectivity and sustainable urban mobility in this regard. It is a qualitative approach, including interviews with stakeholders, observation on the field and survey of 400 tourists, both domestic and international. Thematic analysis based on GIS spatial mapping was utilized to analyze accessibility gaps and to develop strategic routes. The results indicate that there is a strong support from public and institutional to introduce a technology-based monorail system that will connect Nongsa-Batam Center-Harbour Bay as the main tourism nodes. Its potential integration with Intelligent Transportation Systems (ITS) and Smart Tourism concepts further emphasizes its importance in improving efficiency, equity, and the experience of the visitors. This paper makes conceptual contributions by linking spatial–qualitative methods and smart transport design in the context of mid-sized cities in Southeast Asia, and offers practical policy implications for tourism-based sustainable mobility innovation in Batam.